Productividad Primaria y Crecimiento de Carpas Chinas en Estanques Rústicos - Molina Astudillo, Isela; Granados-Ramírez, José Guadalupe; Quiroz-Castelán, Héctor (Acta Universitaria, 2003)
The objective of this project was to know the primary productivity, the transparency, pH, dissolved oxygen and carbon dioxide and its relation with growth of two species of cyprinids Ctenopharyngodon idella and Cyprinus carpio rubrofruscus in three rustic ponds, two ponds with Macrobrachium rosenbergii. The rustic ponds were fertilized with liquid cow manure. This project was carried out at the “El Jicarero” fish farm in Jojutla, Morelos. The results of the composition and abundance of phytoplankton besides chlorophyll “a” concentrations and physico-chemical parameters, showed not significant differences (P>0.05); the values of weigth length of the cyprinids showed significant differences (P <0.05). The correlation coefficients of phytoplankton and fertilizer with transparency, dissolved oxygen and carbon dioxide were significant.